Pengaruh Disiplin Kerja, Keselamatan Dan Kesehatan Kerja, Serta Lingkungan Kerja Terhadap Pruduktivitas Karyawa UD. Syafaat Prambon - Mohamad Irvan Sayfulloh; Ustadus Sholihin; Zulfia Rahmawati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
Human Resource Management (HRM) is a way to provide employees with an understanding of how to develop employment opportunities, work groups that have the appropriate capacity to provide appreciation for their efforts and work. This is because HR is tasked with realizing the vision and mission of a company. By taking a sample of 35, namely all UD employees. Syafaat Prambon with correlation and regression analysis techniques. The results of the analysis concluded: 1) Work Discipline has a positive and significant effect on UD employee productivity. Prambon Intercession. 2) Occupational Safety and Health has a negative and significant effect on the productivity of UD Syafaat Prambon employees. 3) The work environment has a positive and significant effect on UD employee productivity. Prambon Intercession. 4) Simultaneously, it is known that there is a significant influence between work discipline, work safety and health, and the work environment on the productivity of UD employees. Prambon Intercession.